When the light of knowledge (ulama) fades - Musa, Norwahida (Universiti Teknologi MARA, Kedah, 2025)
In the Islamic tradition, knowledge is revered as a guiding light, illuminating paths of righteousness, justice, and understanding. Scholars, or ulama, are entrusted with preserving, interpreting, and transmitting this knowledge, acting as pillars of ethical and spiritual guidance. The diminishing presence of ulama today raises concerns about the potential consequences on moral direction, unity, and intellectual depth within the Muslim community. This paper explores the vital role of ulama and the effects their absence could have, drawing on recent interpretations of classical teachings to underscore the significance of maintaining this “light of knowledge.”